The Pocket Business Communicator: A Complete A-Z of Ready-Made Business Letters And Documents - Shirley Taylor
This reference text and disk contain approximately 120 specimens of all the main business documents, with guidelines on effective writing, tone, style, language and layout. Includes an agenda; business letter layout; CV; e-mail; employment application; job description; memo; press release; newsletter; questionnaire; report; redundancy notification; salary increases; staff circulars; tear-off slip; and unwelcome news.